How readers engage with newspaper advertising - Foster, Anne (Henry Stewart Talks, 2010)
Newspapers as a medium to deliver mass reach and consumer immersion, Newspapers' role as 'social fuel', The implications for advertisers in optimizing communication via newspaper advertising, Specific characteristics of the male and female audiences, Examples of effective advertising
Archived at 2022/11/27